(untitled) (Nepal Medical College Journal, 2025)
Maternal nutrition during pregnancy significantly impacts fetal health in the long term. Inadequate nutrient intake can lead to maternal anemia, which increases the risk of other complications and maternal mortality. It can also result in fetal growth retardation and low birth weight. Both the quality and quantity of nutrition are crucial during this critical period. The current study aimed to analyze the relation between maternal dietary patterns and infant birth outcome among Nepalese mother. This study was hospital-based birth cohort prospective study. Ethical approval was taken from Paropakar Maternity and Women’s Hospital (Ref no: 63/1180). It was conducted from March 2023 to December 2024 at Paropakar Maternity and women’s Hospital. A total of 367 participants were recruited for the study. The pregnant women who attended ANC OPD at 20 to 26 weeks of gestation were selected. Convenience sampling method was used. Dietary intake assessment was done and the pregnancy outcomes was recorded after delivery. Descriptive statistics, chi-square (χ2) test, and Manova Test was applied. Dietary assessments showed higher adequate consumption of pulses, green leafy vegetables, and dairy products, with a significant relationship (p = 0.001) between dietary adequacy and fetal macrosomia, despite only 4.3% of neonates being macrosomic. Maternal age and occupation had no significant impact on delivery outcomes, and neither did smoking, alcohol, or chronic diseases. Adequate dietary diversity was associated with better mode of delivery outcomes, though it did not significantly affect other neonatal outcomes. Maternal nutrition, particularly dietary diversity, is crucial for neonatal outcomes, with significant associations found for adequate food consumption and delivery outcomes, while other maternal factors showed no significant effects.